Dense topological groups in Parovičenko spaces - Argangel’skii, A. V.; van Mill, J. (Topology Proceedings, 2021)
We show that the statement 'the Cech-Stone remainder of the discrete space $ω$ contains a dense subspace which is (homeomorphic to) a topological group' is not a statement of ZFC. We also discuss the question of whether this result can be extended to Parovičenko spaces.